Features of leukocytes’ apoptosis and emoxypine succinate efficacy in case of combined trauma of the chest and both thighs in rats - Krynytska, Inna; Marushchak, Mariya; Holovatiuk, Liudmyla; Shkrobot, Leonid; Sokhor, Natalia; Stepas, Julia (Bangladesh Journal of Medical Science, 2019)
Objective: This study aims to establish features of blood leukocytes’ apoptosis and substantiate the efficacy of emoxypine succinate applying in case of combined trauma of the chest and both thighs in rats. Materials and Methods: Analysis of cell samples to determine reactive oxygen species was evaluated by the flow laser cytometry method, using 2.7-dichlorodihydrofluorescein diacetate (Sigma Aldrich, Germany). The number of leukocytes with low mitochondrial transmembrane potential was evaluated by the flow laser cytometry method, using a kit of reagents «MitoScreen» («BD Pharmingen», USA). The number of apoptotic leukocytes was evaluated by the flow laser cytometry method, using a kit of reagents “ANNEXIN V FITC” (“Beckman Coulter”, USA). Emoxypine succinate to animals was injected intraperitoneally 1 time per day during 14 days from the first day of experiment in the dosage of 40 mg/kg. Results and Discussion: It was established the progressive, statistically significant increasing of Annexin V- positive cells percentage from the first day of the combined trauma of the chest and both thighs in rats with the highest values within 7-14 days of observation. On 28 day of experiment the reduction of apoptotic white blood cells percentage by 7.7% than the findings on 14 day was observed, but it remained 33.3% higher than control. The analysis of data in case of emoxypine succinate applying indicates that production of reactive oxygen species by leukocytes began to decline after 3 days of experiment and continued to decrease with maximum of action on 7 day. On 28 day of experiment the production of reactive oxygen species by leukocytes has decreased by 39.8 %; the percentage of leukocytes with low transmembrane potential has decreased by 34.6 % vs rats without medical treatment. At the same time the dynamics of FITC Annexin V- positive leukocytes changes in case of combined trauma of the chest and both thighs in rats and emoxypine succinate applying on 28 day of experiment has decreased by 16.7 % vs rats without medical treatment. Conclusion: One of important signaling pathways of apoptosis triggering in case of experimental combined trauma of the chest and both thighs is reactive oxygen species overproduction and disruption of the mitochondrial inner membrane due to the decreasing of transmembrane potential in 3-7 days of observation. Emoxypine succinate applying in post-traumatic period has a positive effect, characterized by decreasing of the production of reactive oxygen species, the percentage of leukocyte with low mitochondrial transmembrane potential and the percentage of FITC Annexin V- positive cells of leukocyte suspension. But the dynamics of FITC Annexin V- positive leukocytes changes leads us to believe that in the initiation and implementation of cell death in case of combined trauma apart mitochondrial, there are other mechanisms. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.244-251